Comprehensive Analysis of the Relationship Between Leisure Constraints Negotiation and Leisure Participation Within the Korean Context - Kim, Eui Jae; Park, Seong Man; Kang, Hyun Wook (Frontiers in Psychology, 2022)
The purpose of this study was to identify relationship between leisure constraint negotiations and leisure activity participation through meta-analysis within the Korean context. Through this study, the inconsistent research results of previous studies are explained by comprehensively clarifying the relationship between the two variables and identifying a third variable that controls the relationship. The efforts of this project are expected to provide useful data that can be used for future research and to seek ways of increasing participation in leisure activities. In order to achieve the purpose of this study, the research questions set in this study are as follows. First, what is the magnitude of the effect of the correlation coefficient between leisure constraint negotiations and leisure participation? Second, what are the variables that control the relationship between leisure constraint negotiations and leisure participation? Materials were collected by utilizing Research Information Sharing Service, DBpia, Korean studies Information Service System, and Korea Citation Index. Finally, 20 pieces of research materials were selected with a total of 6,843 participants. The conclusions drawn from the research questions set in this study are as follows. First, leisure constraint negotiations and leisure participation are in a static relationship, and their level is considerable. In other words, efforts to overcome leisure constraints increase participation in leisure activities. Second, gender, age, and type of active leisure activities are major variables that control the relationship between leisure constraint negotiations and leisure participation. Finally, the limitation of this study and future research orientation were discussed.